Gaya xiquexiquensis (Malvaceae, Malvoideae), a new species from Bahia state, Brazil - Takeuchi, Catia; Esteves, Gerleni Lopes (Phytotaxa, 2015)
Gaya xiquexiquensis is a new species from the state of Bahia, Brazil. This species is known only from the municipality of Xique-Xique, growing in the Caatinga biome of the Brazilian semi-arid region. Gaya xiquexiquensis is morphologically similar to Gaya aurea A. St.-Hil. We here in present its morphological description, illustrations, as well as ecological data and conservation status.